Mitogen-Activated Protein Kinase Pathway: Genetic Analysis of 95 Adrenocortical Tumors. (26th November 2015) - Rubin, Beatrice; Monticelli, Halenya; Redaelli, Marco; Mucignat, Carla; Barollo, Susi; Bertazza, Loris; Mian, Caterina; Betterle, Corrado; Iacobone, Maurizio; Fassina, Ambrogio; Boscaro, Marco; Pezzani, Raffaele; et al.
Abstract : Mitogen-activated protein kinase (MAPK) pathway is often deregulated in adrenocortical tumors (ACT) but with no concrete data confirming alteration rate. The objective of this study was to evaluate genetic alterations in key components of MAPK pathway. We found one BRAF mutation (p.V600E) and four HRAS silent mutations. No alteration was found in NRAS, KRAS, EGFR genes. The patient carrying BRAF mutation was further characterized by investigating his biomolecular and clinico-pathological findings. Therefore, even if MAPK signaling is activated in ACT, our results suggest that genetic alterations do not seem to represent a frequent mechanism of ACT tumorigenesis.